Research on Sustainable Development of Competitive Sports in China Based on PSR and DEA Model - Zhang, Su; Ouyang, Tong; Wei, Shou-Yu; Liang, Bei-Bei; Zhu, Jia-Ming (Frontiers in Psychology, 2022)
Since the 2008 Beijing Olympic Games to the 2022 Beijing Winter Olympics, the sustainable development of competitive sports has become more and more popular in China. Therefore, for the sustainable development of China’s competitive sports, firstly, the logical relationship of “pressure-state-response” is adopted to select the index system, covering the elements of economy, society, policy and so on. Principal component analysis and entropy weight method are used to construct the comprehensive evaluation model of the sustainable development of competitive sports. Secondly, through the coupling coordination method to study the coordinated development of China’s competitive sports and economic society, and then from the perspective of the obstacle factor diagnosis method to determine the obstacles to the sustainable development of China’s competitive sports system. Finally, DEA model is used to predict the development level of competitive sports in China’s provinces in the next 10-20 years. The research shows that the overall development level of competitive sports in China is good, but there are certain differences among different regions. Meanwhile, from the forecast results, the development level of competitive sports in hainan, Shanxi, Anhui, Jiangxi, Inner Mongolia, Gansu and Ningxia may be greatly improved in the future. Based on the above research conclusions, this paper puts forward some suggestions to give full play to the joint and synergistic development effect among different regions, reasonably draw lessons from the advanced experience of competitive sports development at home and abroad, and scientifically construct the comprehensive development system of competitive sports. At the same time, the research of this paper provides some reference value for the sustainable development of China’s competitive sports and the coordinated development of China’s competitive sports and economic society.